Report from MeSH Information Group Updated MeSH: what’s new for 2015 (Journal of EAHIL, 2015)
As already witnessed over the past years, MeSH update for 2015 focused on leading subject areas,Â introducing key terms in scientific research fields.Â The rising interest for molecular biology has progressively shifted...